The arachnid order Schizomida in the Brazilian Atlantic Forest: a new species of Rowlandius and new records of Stenochrus portoricensis (Schizomida: Hubbardiidae) - Santos, Adalberto J.; Dias, Sidclay C.; Brescovit, Antonio D.; Santos, Pollyanna P. (Zootaxa, 2008)
Two species of hubbardiid microwhipscorpions (Schizomida: Hubbardiidae) are recorded from the Brazilian Atlantic Forest. Rowlandius linsduarteae sp. nov. is described and illustrated based on specimens from Mata do Buraquinho forest reserve, João Pessoa, state of Paraíba, northeastern Brazil. This species is apparently related to Rowlandius sul Cokendolpher & Reddell 2000, the only species of the genus known from continental South America, and represents new evidence of a biogeographic relationship between Amazonia and the northeastern Brazilian Atlantic Forest. Stenochrus portoricensis Chamberlin, a widely distributed species, is newly recorded from the states of São Paulo and Bahia, respectively, in southeastern and northeastern Brazil. The latter record refers to several female specimens associated with abandoned arboreal termite nests in a cocoa plantation.